Дослідження у Луцьку на вул. Гнідавській - Златогорський, О.Є.; Панишко, С.Д. (Археологічні дослідження в Україні, 2009)
Archaeological research in Lutsk at the Hnidavska Street resulted in the discovery of an Early Iron Age hearth of complicated construction and an Ancient Rus period husbandry pit, despite of partially destruction of a monument during the reburial of the victims of the World War II.